Development of a Graph-Based Tool for Planning of District Heating Network - Nguyen, Ngoc Thuy Linh (My University, 2026)
As cities look for practical ways to reduce fossil-fuel use in heating, district heating offers a shared infrastructure through which buildings can be connected to more efficient and renewable heat sources. The planning of such networks is especially challenging when they are expected to grow ever time, because each new consumer or heat source can change the pressure, flow, temperature, and cost profile of the whole system. This thesis develops HeatNet, a transparent graph-based pre-design tool for testing radial district-heating networks before detailed engineering design is carried out. The tool represents the supply and return network as a radial tree and combines topology validation, demand-based flow estimation, pipe sizing, hydraulic balancing, thermal propagation, final-state checking, and distribution-side cost comparison in one reproducible workflow. It is applied to reference expansion cases and to a campus-scale case study at the University of Mons, using network layouts derived from geographic data and heat-demand information from building consumption records. The results show that HeatNet can compare alternative radial layouts, reveal when a passive single-pump network becomes hydraulically weak, and indicate balancing valves as a practical correction when short loops are overdriven. The thesis concludes that a topology-aware graph formulation is a useful basis for early-stage district-heating planning, particularly when several expansion or supply scenarios must be compared before committing to a final design.
Keywords: district heating; thermal hydraulics; pipings; hydraulics; community planning; topology; networks (societal phenomena); renewable energy sources; fi=Energiatekniikka, DI|en=Energy Engineering|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|en=Degree Programme in Electrical Engineering and Energy Technology|